2013
DOI: 10.1186/1471-2482-13-s2-s16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and dietary prevention for colorectal cancer

Abstract: BackgroundColorectal cancer (CRC) is a leading cause of cancer morbidity and mortality. People at higher risk are those individuals with a family history of CRC and familial adenomatous polyposis. Prevention and screening are two milestones for this disease. The aim of this study is to evaluate the chemopreventive role of non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin and cyclooxygenase 2 inhibitors, some micronutrients (folic acid, calcium, selenium, antioxidants) and probiotics.DiscussionT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 118 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…Se content in lyophilised snail tissues was a little bit lower than in dry matter of beef [ 18 ] and edible parts of oysters [ 37 ]. In the work of Nolfo et al, the potential prevention of colorectal cancer by Se was attributed to its functions in acceleration of DNA repair, reduction of DNA damage and decrease in mutations contributing to carcinogenesis [ 63 ]. Another mechanism could be related to induction of apoptosis, by the activation of Caspase-3 and modulation of glutathione and functions of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Se content in lyophilised snail tissues was a little bit lower than in dry matter of beef [ 18 ] and edible parts of oysters [ 37 ]. In the work of Nolfo et al, the potential prevention of colorectal cancer by Se was attributed to its functions in acceleration of DNA repair, reduction of DNA damage and decrease in mutations contributing to carcinogenesis [ 63 ]. Another mechanism could be related to induction of apoptosis, by the activation of Caspase-3 and modulation of glutathione and functions of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 expression and its downstream by-product, prostaglandin E 2 (PGE 2 ), are upregulated in sporadic CRC and IBD [ 6 ]. Moreover, COX-2 inhibitors have been shown to reduce carcinogenesis in both animal and human studies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of interest in naturally occurring substances found in food for CRC prevention (3) ; two such agents of interest are Se, an essential trace micronutrient, and green tea, the second most widely consumed beverage in the world next to water (4) . Epidemiological and observational studies have identified the association between Se and/or green tea supplementation with risk of CRC (5)(6)(7)(8) . Although preclinical studies have shown promising results in this regard, a few studies on Se or green tea have demonstrated their effectiveness as cancer preventive agents in human clinical trials (7,9) .…”
mentioning
confidence: 99%
“…Dietary agents generally have a favourable safety profile, with good accessibility, low costs and strong biological plausibility, although they often have less potency compared with pharmaceutical compounds (14) . There is a growing interest for improving efficacy of cancer prevention by combination of dietary agents with complementary mechanisms (5) . The Linxian Chinese Cancer Prevention Trial (targeting 29 584 adults) showed that a combination of β-carotene, vitamin E and Se Abbreviations: Ac-H3, acetylated histone H3; CRC, colorectal cancer; DNMT, DNA methyltransferase; EGCG, (-)-epigallocatechin-3-gallate; GTE, green tea extract; SePP, selenoprotein P.…”
mentioning
confidence: 99%